ECOLOGY AND BEHAVIOR OF COATIS Nasua nasua (LINNAEUS, 1766) IN AN URBAN PARK IN SOUTHERN BRAZIL: Ecology and behavior of coatis Nasua nasua - Milleo, Gabriel Brambila (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2024)
The Atlantic Forest has important environmental heterogeneity and biodiversity, thus it is recognized as one of the most critical global ecological regions. Coatis Nasua nasua are found in urban forest fragments and urbanized areas and use available green spaces and human-provided resources and so are a good model to study the influence of anthropogenic environments. The aim of this study was to investigate the effects of urbanization and forest fragmentation on the ecology and behavior of coatis (Nasua nasua) in Arthur Thomas Municipal Park, Londrina, Paraná, Brazil. Ecology and behavior include population size, daily activity patterns and habitat use obtained through active search and direct visualization of individuals and their tracks. Population density was estimated at 36.1 individuals per km2 and is greater than estimates in natural areas, probably due to anthropogenic food sources and the absence of top predators. Coati activity was greatest between 08:00 and 13:00 h when they tend to be terrestrial. Forested habitat was the most used, followed by secondary vegetation, and coatis used different the areas of the park in different ways during the dry and rainy periods, with a wide use of anthropogenic areas in all periods, closely related to the contribution of food of anthropic origin.